Beyond Aggravating and Mitigating Factors: The Analysis of Colorado's Death Penalty Cases (1999-2010):. (3rd July 2021) - Okpara, Chinyere; Hendricks, Audrey E.; Cobb, Loren
Abstract: In Colorado, studies have shown that the likelihood of the prosecutions' decision to pursue the death penalty is related to the defendant's race and judicial district of the trial. These studies examined race and district separately without incorporating aggravating or mitigating factors resulting in others questioning the studies' validity. Our objective is to address these concerns by modelling race and population density together along with applied aggravating and mitigating factors. We found that the likelihood of the prosecutions' decision to pursue the death penalty differs by the number of aggravating factors applied to a case, applicability of specific aggravating factors, and the defendant's race. Additionally, there were aggravating factors that were frequently applied yet did not predict the average prosecution's decision to pursue the death penalty beyond contributing to the overall number of aggravating factors applied to the case.